Fusion and planarization of a quinoidal porphyrin dimer. - Blake, I; Krivokapic, A; Katterle, M; Anderson, H (2002)
The crystal structure, near-infrared spectrum and electrochemistry of a quinoidal triply-linked porphyrin dimer are compared with those of its singly-linked precursor; fusing the two porphyrins planarizes the pi-system and reduces the optical HOMO-LUMO gap while increasing the gap between the first oxidation and reduction potentials.